Strategi Peningkatan Kinerja PT BPR BKK Purwokerto (Perseroda) Berbasis MBCfPE - Yoiz Shofwa Shafrani; Arzeti Ika Febrianti; Eili Widiyastuti; Hanifah Nabila (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to identify and formulate a strategy to improve the performance of PT Bank Perkreditan Rakyat (BPR) BKK Purwokerto (Perseroda) using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE). Facing tight competition in the financial sector, PT BPR BKK Purwokerto (Perseroda) needs to implement a systematic approach to improve operational efficiency and service quality. This study uses a literature study method and in-depth interviews with management and employees to collect data and analyze current conditions and potential improvements. The results of the study indicate that the application of Malcolm Baldrige principles, such as market and customer focus, has a positive impact on the performance of PT BPR BKK Purwokerto (Perseroda). Human resource development and product innovation have also been proven to be major supporting factors. Employee involvement in decision making increases motivation and productivity, which contributes to customer satisfaction. Therefore, PT BPR BKK Purwokerto (Perseroda) is advised to implement this strategy comprehensively to achieve sustainable competitive advantage.